Integrating transdisciplinary literacies into higher education - Eybers, O. O. (South African Journal of Higher Education, 2025)
Transdisciplinary teaching, learning and philosophical dialogues have long been a part of global higher education, yet their significance is increasingly being recognised today. The concept of transdisciplinary philosophy, particularly within the context of an academic literacy framework, involves the integration and synthesis of knowledge from across various disciplines, in collaboration with local communities, to address real-life challenges. Despite the growing prominence of transdisciplinary teaching, learning and assessment methods, there remains a knowledge gap that explicitly connects these processes to academic literacy. This gap, which the article addresses, is significant as transdisciplinary literacies – including critical thinking, reading, listening and writing – are crucial mediums through which teachers, researchers, students and local stakeholders cultivate knowledge. To explore the role of transdisciplinary literacy within higher education, the researcher undertook a systematic review of literature to identify instances where academic literacies intersect with disciplinary, and communities' activities. Academic literacies intersect with transdisciplinary approaches in the ways knowledge is constructed and how culture influences the spread of disciplines into greater society. To maximise the potential of transdisciplinary literacies in enhancing knowledge generation in higher education, this article advocates for more strategic interactions between academic literacy specialists, disciplinary experts, local communities and industrial stakeholders.